Diabetes Retinopathy Prevalence and Risk Factors among Diabetic Patients Seen at Highland Eye Clinic Mutare Zimbabwe: A Retrospective Study - Tatenda Lewis, Musokeri; Mena, Wani; Salissou, Maibouge Tanko Mahamane (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To determine the prevalence of diabetic retinopathy and its association with hypertension, age, gender, and fasting blood glucose level.Methods: This retrospective study assessed the prevalence of diabetic retinopathy with its associated risk factors on 135 diabetic patients, aged 18 years and above, visiting the Highland Eye Clinic Mutare, Zimbabwe. Data were collected on the age, sex, and type of retinopathy. Based on the identified retinopathy, subjects were divided into no retinopathy, non-proliferative diabetic renopathy, and proliferative diabetic retinopathy groups. Analysis were then performed using multivariate and univariate regression analyses to test the association between the presence of retinopathy and several risk factors, and results were presented in percentages, with P< 0.05 considered to show statistical significance.Results: The average age of the subjects this study was 60.8 ± 14 with female subjects constituted more than half of the total number of subjects (58.5%). Forty four percent were overweight (BMI 25-30), 34.8 % were obese, and the overall prevalence of diabetic retinopathy was 31.1% (non-proliferative diabetic renopathy, 20%; proliferative renopathy, 11.1%). The proportion of subjects with retinopathy increased with duration of DM, being 23.3% in those with a DM duration of less than 10 years and 46.6% in those with a DM duration of more than 10 years. Age and hypertension were significantly associated with the presence of diabetic retinopathy (P< 0.05) in univariate analysis, but no association was identified between retinopathy and fasting blood glucose (chi-square test, P =0.0965)Conclusion: The prevalence of diabetic retinopathy (DR) is high (31.1%), Non-proliferative DR is more common than the proliferative (DR). There is a strong association between diabetic retinopathy, hypertension, and age.